Ritual, routine and regime : repetition in early modern British and European cultures - Clymer, Lorna, 1955- (UCLA Clark Memorial Library series., 2006)
Providing a stimulating, new perspective on early modern culture, the collection describes repetition's often peculiar demands, its surprising gratifications, and its contested interpretations.